Method for preparing and forming titanium lithium ion sieve

In the preparation process of titanium lithium ion sieve, industrial grade metatitanic acid calcination and dehydration and solid phase reaction of molten salt medium, combined with acid leach, centrifugation and binder treatment, the metatitanic acid ion sieve composite particles are formed, solving the problems of high titanium dissolution loss rate and low recovery rate, and achieving efficient lithium ion adsorption and low cost resource recovery.

CN119549106APending Publication Date: 2025-03-04EAST CHINA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411835559.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing titanium lithium-ion sieve has a high titanium dissolution loss rate during the acid desorption process, resulting in a decrease in the lithium adsorption rate and adsorption amount. At the same time, its fluidity and permeability are poor, the recovery rate is low, and the recovery cost is high.

Method used

Anatase-type titanium dioxide is obtained by calcining and dehydration of industrial grade metatitanic acid, and solid phase reaction with lithium carbonate under a molten salt medium to obtain lithium titanate precursor. The metatitanate ion sieve powder is obtained by acid illumination, centrifugation, drying and grinding, and then mixed with a binder, pore-making agent and organic solvent to form metatitanate ion sieve composite particles, and the final product is obtained by acid elution and neutralization treatment.

Benefits of technology

The titanium dissolution loss rate is reduced, the lithium ion adsorption rate and adsorption amount is improved, the mechanical strength and microporous structure of the metatitanate ion sieve composite particles are enhanced, the contact area with brine is ensured, the lithium extraction speed and recovery rate are improved, and the recovery cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549106A_ABST
    Figure CN119549106A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation and forming method of a titanium lithium ion sieve. The preparation and forming method of the titanium lithium ion sieve comprises the following steps: (S1) calcining and dehydrating industrial-grade metatitanic acid to obtain anatase titanium dioxide; (S2) carrying out solid-phase reaction on the anatase titanium dioxide and the reaction material lithium carbonate under a molten salt medium to obtain an ion sieve precursor lithium titanate; (S3) carrying out acid leaching on the ion sieve precursor lithium titanate, centrifuging, drying and grinding to obtain metatitanic acid ion sieve powder; and (S4) mixing the metatitanic acid ion sieve powder, an adhesive, a pore-forming agent and an organic solvent, dispersing the mixture into a water phase, and carrying out pickling impurity removal and neutralization treatment to obtain the metatitanic acid ion sieve composite particles. The method has the advantages that the ion sieve precursor lithium titanate grows in the molten salt medium during high-temperature calcination so as to inhibit grain aggregation, the titanium loss generated by the metatitanic acid ion sieve composite particles during brine lithium extraction only causes grain size reduction, but the original layered structure is not changed, and the recovery operability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium-based lithium ion sieves, and in particular to a preparation and molding method of a titanium-based lithium ion sieve. Background Art

[0002] As one of the important materials for green energy in the new century, the development and application of lithium has attracted much attention from all countries. At present, the industrial practical value of lithium extraction from brine by adsorption method is the greatest, but the key to the application of adsorption method is to synthesize adsorbents with excellent performance. The current adsorbents are mainly aluminum salt adsorbents, manganese ion sieves and titanium ion sieves. Based on the chemically stable Ti-O bond, the titanium lithium ion sieve has good structural stability under acid desorption conditions and can be used in a long-term cycle. In addition, the titanium element is non-toxic and easy to separate, and it is not easy to cause secondary pollution to the environment, so it has good industrial application prospects.

[0003] A variety of ion sieve precursor synthesis methods have been reported, including solid phase synthesis. The traditional solid phase synthesis method is to prepare the ion sieve precursor lithium titanate by high temperature calcination of lithium carbonate and anatase titanium dioxide mixture. In order to reduce the titanium dissolution loss rate of the layered structure ion sieve precursor lithium titanate during acid desorption, the optimal solid phase calcination reaction temperature is about 1023-1073K. However, high temperature calcination will cause the ion sieve precursor lithium titanate grains to aggregate, resulting in a decrease in the lithium adsorption rate and adsorption amount of the metatitanate ion sieve powder.

[0004] In addition, the fluidity and permeability of the titanate ion sieve powder itself are relatively poor, resulting in large losses during lithium extraction from brine, low recovery rates, and high recovery costs. Summary of the invention

[0005] In order to solve the above technical problems and achieve at least one advantage of the present invention, the present invention provides a method for preparing and molding a titanium-based lithium ion sieve, the method for preparing and molding a titanium-based lithium ion sieve comprising:

[0006] (S1) Anatase titanium dioxide is obtained by calcining and dehydrating industrial grade metatitanic acid;

[0007] (S2) performing a solid phase reaction of anatase titanium dioxide and a reaction material, lithium carbonate, in a molten salt medium to obtain an ion sieve precursor, lithium titanate;

[0008] (S3) acid leaching lithium titanate, an ion sieve precursor, and centrifuging, drying, and grinding to obtain metatitanate ion sieve powder;

[0009] (S4) Titanate ion sieve powder, a binder, a pore-forming agent and an organic solvent are mixed and dispersed into an aqueous phase after mixing to form impurity-containing titanium ion sieve composite particles, and the impurities are removed by acid washing and neutralization treatment to obtain titanium ion sieve composite particles.

[0010] According to an embodiment of the present invention, the calcination temperature in the step (S1) is 873.15-923.15K, and the calcination time is 3-5 hours.

[0011] According to an embodiment of the present invention, the step (S2) includes the following steps:

[0012] (S21) grinding and mixing anatase titanium dioxide, a reaction material lithium carbonate and a molten salt medium to obtain a molten salt mixed system reaction material;

[0013] (S22) The molten salt mixed system reactants are calcined to react and obtain the ion sieve precursor lithium titanate.

[0014] According to one embodiment of the present invention, the molten salt medium includes lithium chloride and lithium hydroxide, the molar ratio of the reaction materials lithium carbonate to anatase titanium dioxide is 1:1, and the molar ratios of lithium chloride and lithium hydroxide to anatase titanium dioxide in the molten salt medium are 1.53-1.81:1 and 0.27-0.33:1 respectively.

[0015] According to an embodiment of the present invention, the calcination temperature in the step (S22) is 1023.15-1073.15K, and the calcination time is 8-10 hours.

[0016] According to an embodiment of the present invention, the step (S3) includes the following steps:

[0017] (S31) mixing the ion sieve precursor lithium titanate with hydrochloric acid for desorption, taking out the acid leaching solution containing lithium chloride obtained by desorption of the upper layer and adding hydrochloric acid to repeat desorption to obtain a layered powder product after desorption;

[0018] (S32) The desorbed layered powder product is centrifuged to obtain a titanate ion sieve powder block, and the titanate ion sieve powder block is dried and ground in turn to obtain a titanate ion sieve powder.

[0019] According to one embodiment of the present invention, the extracted acid leaching solution containing lithium chloride is evaporated and crystallized to obtain lithium chloride, which is used as the molten salt medium required in step (S21).

[0020] According to an embodiment of the present invention, the step (S4) includes the following steps:

[0021] (S41) mixing the titanate ion sieve powder, the binder, the pore-forming agent and the organic solvent to obtain a mixed slurry;

[0022] (S42) sucking the mixed slurry and injecting it into water to form impurity-containing metatitanate ion sieve composite particles in the water phase;

[0023] (S43) The impure titanate ion sieve composite particles are impregnated with hydrochloric acid and then washed with a weak alkaline aqueous solution to obtain neutral titanate ion sieve composite particles.

[0024] According to one embodiment of the present invention, the adhesive is implemented to include polyvinyl butyral and polyacrylonitrile, the pore-forming agent is implemented as lithium carbonate powder, the organic solvent is implemented as N,N-dimethylacetamide, the titanate ion sieve powder is 11.7-14.3g, the corresponding polyvinyl butyral is 3.15-3.85g, the polyacrylonitrile is 0.45-0.55g, the lithium carbonate powder is 0.27-0.33g, and the N,N-dimethylacetamide is 16.2-19.8ml.

[0025] According to one embodiment of the present invention, waste titanate ion sieve composite particles are recovered, dried and the content of titanate ion sieve powder therein is measured, dissolved by an organic solvent, a pore-forming agent is added according to a predetermined proportion, and titanate ion sieve powder is added according to the difference between the predetermined proportion and the calculated titanate ion sieve powder to mix them, and then steps (S42) and (S43) are performed to obtain new titanate ion sieve composite particles.

[0026] Compared with the prior art, the preparation and molding method of the titanium-based lithium ion sieve of the present invention has the following technical effects:

[0027] 1. Use industrial-grade metatitanic acid to calcine and dehydrate to obtain anatase titanium dioxide as a titanium source. Since the cost of industrial-grade metatitanic acid is relatively low, the cost of obtaining the titanium source is also relatively low, which meets the requirements of large-scale mass production.

[0028] 2. Anatase titanium dioxide and the reaction material lithium carbonate undergo a solid phase reaction in a molten salt medium. While ensuring that the titanium dissolution loss rate is sufficiently low when used for lithium extraction from brine, the molten salt medium is used to inhibit grain aggregation, achieving the goal of small and uniform nano-grain size.

[0029] 3. By making the metatitanate ion sieve powder into metatitanate ion sieve composite particles, its mechanical strength is improved, and its rich microporous structure ensures the contact area with the brine, thereby ensuring the lithium extraction speed.

[0030] 4. The titanium loss of the prepared metatitanate ion sieve composite particles in the process of extracting lithium from brine only causes the grains to become smaller, but the original layered structure remains unchanged, which increases the ease of recycling. In addition, by recycling and reshaping the waste metatitanate ion sieve composite particles, the recycling and reuse of resources can be achieved, so as to effectively reduce the application cost.

[0031] 5. When the calcination temperature of the ion sieve precursor lithium titanate is 1023K, the capacity of the obtained metatitanate ion sieve composite particles to adsorb lithium ions is 28.13mg / g, and the titanium loss is 0.193%. At this time, the metatitanate ion sieve composite particles have a large enough amount of lithium ion adsorption, and the titanium loss is relatively small. In addition, at this calcination temperature, the lithium ion adsorption and titanium loss do not change due to the preparation amount of the metatitanate ion sieve composite particles, which meets the requirements of large-scale brine lithium extraction operations.

[0032] 6. The acid leaching solution containing lithium chloride produced in the process of making metatitanate ion sieve powder from lithium titanate, the precursor of ion sieve, is evaporated and crystallized to obtain lithium chloride, which is used as a component of the molten salt medium to achieve recycling and save production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The XRD patterns of the ion sieve precursor lithium titanate, the metatitanate ion sieve powder, the powder after use, and the monoclinic β-Li2TiO3 are shown.

[0034] Figure 2 The SEM and TEM images of the metatitanate ion sieve powder, the cross section of the metatitanate ion sieve composite particles and the SEM image after the cross section is enlarged are shown. Figure 2 The middle is the SEM image of metatitanate ion sieve powder. Figure 2 middle This is the TEM image of metatitanate ion sieve powder. Figure 2 middle This is the SEM image of the cross section of the metatitanate ion sieve composite particles. Figure 2 middle This is an enlarged SEM image of the cross section of the metatitanate ion sieve composite particles.

[0035] Figure 3 A schematic diagram of the test results of lithium ion adsorption and titanium loss rate when lithium ion adsorption tests were carried out on metatitanate ion sieve composite particles prepared from various ion sieve precursor lithium titanates prepared at different calcination temperatures.

[0036] Figure 4 The graph shows the results of measuring the adsorption of different cations by the metatitanate ion sieve composite particles.

[0037] Figure 5 The graph shows the test results of the adsorption of lithium ions by equal amounts of metatitanate ion sieve powder and metatitanate ion sieve composite particles. DETAILED DESCRIPTION

[0038] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art can think of other obvious variations. The basic principles of the present invention defined in the following description can be applied to other embodiments, variations, improvements, equivalents, and other technical solutions that do not deviate from the spirit and scope of the present invention.

[0039] Those skilled in the art should understand that, in the disclosure of the present invention, the terms "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, which are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the above terms should not be understood as limiting the present invention.

[0040] It is to be understood that the term "one" should be understood as "at least one" or "one or more", that is, in one embodiment, the number of an element may be one, while in another embodiment, the number of the element may be multiple, and the term "one" should not be understood as a limitation on the quantity.

[0041] refer to Figures 1 to 4 According to a preferred embodiment of the present invention, a method for preparing and molding a titanium-based lithium ion sieve will be described in detail below. The method for preparing and molding a titanium-based lithium ion sieve includes at least the following steps:

[0042] (S1) calcining and dehydrating industrial-grade metatitanic acid to obtain anatase titanium dioxide as a titanium source for subsequent use;

[0043] (S2) performing a solid phase reaction of anatase titanium dioxide and a reaction material, lithium carbonate, in a molten salt medium to obtain an ion sieve precursor, lithium titanate;

[0044] (S3) acid leaching lithium titanate, an ion sieve precursor, and centrifuging, drying, and grinding to obtain metatitanate ion sieve powder;

[0045] (S4) Titanate ion sieve powder, a binder, a pore-forming agent and an organic solvent are mixed and dispersed into an aqueous phase after mixing to form impurity-containing titanate ion sieve composite particles, and the impurities are removed by acid washing and neutralization treatment to obtain titanate ion sieve composite particles for lithium extraction from brine.

[0046] It is worth mentioning that during high-temperature calcination, the ion sieve precursor lithium titanate grows in a molten salt medium to ensure that the titanium dissolution loss rate is sufficiently low when used in brine lithium extraction. At the same time, the molten salt medium is used to inhibit grain aggregation, achieving the goal of small and uniform nano-grain size, so that the lithium ion adsorption rate and adsorption amount are guaranteed. Due to the poor fluidity and permeability of the titanate ion sieve powder itself, the recovery rate in brine lithium extraction is low, the loss is large, and the recovery cost is high. By making the titanate ion sieve powder into a titanate ion sieve composite particle, the mechanical strength is improved, and the contact area with the brine can also be guaranteed. In addition, the titanium loss caused by the titanate ion sieve composite particles in the brine lithium extraction only causes the grains to become smaller, but the original layered structure does not change, which increases the ease of recovery.

[0047] Preferably, industrial-grade metatitanic acid is calcined at a constant temperature of 873.15-923.15 K for 3-5 hours to dehydrate to obtain anatase titanium dioxide.

[0048] Specifically, the step (S2) includes the following steps:

[0049] (S21) grinding and mixing anatase titanium dioxide, a reaction material lithium carbonate and a molten salt medium to obtain a molten salt mixed system reaction material;

[0050] (S22) The molten salt mixed system reactants are calcined to react and obtain the ion sieve precursor lithium titanate.

[0051] Preferably, the molten salt medium is implemented to include lithium chloride and lithium hydroxide.

[0052] Preferably, the molar ratio of lithium carbonate to anatase titanium dioxide in the reaction materials is 1:1, and the molar ratios of lithium chloride and lithium hydroxide to anatase titanium dioxide in the molten salt medium are 1.53-1.81:1 and 0.27-0.33:1 respectively.

[0053] Preferably, the molten salt mixed system reaction materials are calcined at a high temperature of 1023.15-1073.15K for 8-10 hours.

[0054] Specifically, the step (S3) includes the following steps:

[0055] (S31) mixing the ion sieve precursor lithium titanate with hydrochloric acid for desorption, taking out the acid leaching solution containing lithium chloride obtained by desorption of the upper layer and adding hydrochloric acid to repeat desorption to obtain a layered powder product after desorption;

[0056] (S32) The desorbed layered powder product is centrifuged to obtain a titanate ion sieve powder block, and the titanate ion sieve powder block is dried and ground in turn to obtain a titanate ion sieve powder.

[0057] Preferably, 0.2-0.5 mol / L hydrochloric acid is repeatedly impregnated into the ion sieve precursor lithium titanate at 293.15-303.15 K to extract the lithium ions therein to obtain the analyzed product.

[0058] It is worth mentioning that the acid leaching solution containing lithium chloride is evaporated and crystallized to obtain lithium chloride, which is used as the molten salt medium required for step (S21) and is recycled to save production costs.

[0059] Specifically, the step (S4) includes the following steps:

[0060] (S41) mixing the titanate ion sieve powder, the binder, the pore-forming agent and the organic solvent to obtain a mixed slurry;

[0061] (S42) sucking the mixed slurry and injecting it into water to form impurity-containing metatitanate ion sieve composite particles in the water phase;

[0062] (S43) The impure titanate ion sieve composite particles are impregnated with hydrochloric acid to fully elute the lithium ions inside the particles, and then washed with a weak alkaline aqueous solution to obtain neutral titanate ion sieve composite particles.

[0063] Preferably, the binder is implemented to include polyvinyl butyral and polyacrylonitrile, the pore-forming agent is implemented to be lithium carbonate powder, and the organic solvent is implemented to be N,N-dimethylacetamide.

[0064] In one example, the titanate ion sieve powder is 11.7-14.3 g, the corresponding polyvinyl butyral is 3.15-3.85 g, the polyacrylonitrile is 0.45-0.55 g, the lithium carbonate powder is 0.27-0.33 g, and the N,N-dimethylacetamide is 16.2-19.8 ml.

[0065] Preferably, the metatitanate ion sieve powder, the binder, the pore-forming agent and the organic solvent are mixed into a mixed slurry at a temperature of 303.15-333.15K.

[0066] It is worth mentioning that the waste titanate ion sieve composite particles are recovered, dried and the content of the titanate ion sieve powder therein is calculated, and then they are dissolved by an organic solvent, the pore-forming agent is added according to the proportion in the above example, and the titanate ion sieve powder is added according to the difference between the proportion in the above example and the calculated titanate ion sieve powder to mix them, and then steps (S42) and (S43) are performed to obtain new titanate ion sieve composite particles, so as to realize the recycling and reuse of resources and effectively reduce the application cost.

[0067] The following provides specific examples of the preparation and molding methods of the titanium-based lithium ion sieve of the present invention.

[0068] (S1) Industrial grade metatitanic acid is heated from room temperature (298K) to 923K at a heating rate of 5K / min in hot air at a flow rate of 120mL / min and a temperature of 373K, and is calcined at 923K for 5 hours for dehydration, and then naturally cooled to room temperature at a cooling rate of 10K / min to obtain anatase titanium dioxide;

[0069] (S21) adding the reaction materials lithium carbonate and anatase titanium dioxide in a molar ratio of 1:1 into an agate mortar and grinding for 3 hours, then adding molten salt medium lithium chloride and lithium hydroxide in a molar ratio of 1.7 and 0.3 to anatase titanium dioxide respectively into an agate mortar and grinding for 3 hours to obtain a uniformly mixed molten salt mixed system reaction material;

[0070] (S22) Subsequently, the molten salt mixed system reaction materials are heated from room temperature 298K to 1023K at a heating rate of 5K / min under hot air at a flow rate of 120mL / min and a temperature of 373K, and are calcined at a constant temperature for 10 hours, and then naturally cooled to room temperature at a cooling rate of 10K / min to obtain an ion sieve precursor lithium titanate;

[0071] (S31) The ion sieve precursor lithium titanate is added to 1L of hydrochloric acid at a temperature of 303K and a concentration of 0.5mol / L, and desorbed at a stirring speed of 100prm / min for 3 hours. The acid leaching solution containing lithium chloride obtained by desorption of the upper layer is taken out and hydrochloric acid is added again. The acid leaching operation is repeated 2 to 3 times, and then desorbed twice more using 0.2mol / L hydrochloric acid to obtain a layered powder product after desorption;

[0072] (S32) the desorbed layered powder product is centrifuged in a centrifuge at a speed of 5000prm / min for 15 minutes to obtain a metatitanate ion sieve powder block, the metatitanate ion sieve powder block is vacuum dried at a temperature of 333K for 48 hours, then ground in an agate mortar for 3 hours, and sieved through a 200-mesh sieve to obtain a metatitanate ion sieve powder;

[0073] (S41) stirring 18 ml of N,N-dimethylacetamide with a constant temperature magnetic stirrer at a speed of 200 prm / min, and heating to 323 K for 3 hours, then slowly adding 3.5 g of polyvinyl butyral and 0.5 g of polyacrylonitrile, and stirring at the constant temperature for 6 hours to obtain a uniformly mixed white viscous paste slurry, then adding 0.3 g of lithium carbonate powder to the white viscous paste slurry, and stirring at the constant temperature at 323 K for 4 hours, and then slowly adding 13 g of metatitanate ion sieve powder, and stirring at the constant temperature at 323 K for 10 hours to obtain a mixed slurry;

[0074] (S42) using a syringe with a gun tip to disperse the mixed slurry into 6 L of water phase at a temperature of 298 K at a stirring rate of 300 prm / min to obtain impure metatitanate ion sieve composite particles with a particle size of 1 to 2 mm;

[0075] (S43) The impure titanate ion sieve composite particles are immersed in a 0.2 mol / L hydrochloric acid solution for 3 hours to fully elute the lithium ions inside the particles, and then washed with a potassium bicarbonate aqueous solution with a pH of 7.2 to obtain neutral titanate ion sieve composite particles.

[0076] In addition, the waste titanate ion sieve composite particles are recovered, dried and the content of the titanate ion sieve powder therein is measured, and they are dissolved using N,N-dimethylacetamide, 0.3 g of lithium carbonate is added, and the titanate ion sieve powder is added according to the difference between the proportion in the above example and the calculated titanate ion sieve powder to mix them, and then steps (S42) and (S43) are performed to obtain new titanate ion sieve composite particles.

[0077] Test Example 1

[0078] refer to Figure 1 The waste metatitanate ion sieve composite particles were dissolved in N,N-dimethylacetamide to obtain the used powder. XRD analysis was performed on the ion sieve precursor lithium titanate, metatitanate ion sieve powder and the used powder, and the existing standard XRD spectrum of monoclinic β-Li2TiO3 (JCPDS33-0831) was introduced to obtain the summarized XRD diagram.

[0079] Based on the XRD characterization results of the ion sieve precursor lithium titanate obtained at a calcination temperature of 1023K, its diffraction peaks are 18.469°, 20.165°, 35.861°, 43.582°, 47.754°, 57.565°, 63.486° and 66.735°. These diffraction peak angles are consistent with the standard XRD spectrum of monoclinic β-Li2TiO3.

[0080] In addition, by comparing the characterization results of the ion sieve precursor lithium titanate and the metatitanate ion sieve powder, it can be seen that after the ion sieve precursor lithium titanate was impregnated with a 0.5 mol / L hydrochloric acid solution, the diffraction peaks at (-133) and (-206) disappeared significantly, and the diffraction peaks at (002) and (-131) both moved in the direction of increasing the diffraction peak angle, which indicates that the ion sieve precursor lithium titanate underwent grain shrinkage during the hydrochloric acid impregnation process and replaced the lithium ions.

[0081] In addition, by comparing the characterization results of the titanate ion sieve powder and the powder after use, it can be seen that the peak position of the powder after use corresponds to that of the titanate ion sieve powder, which indicates that the material structure has not changed. It can be seen that the waste titanate ion sieve composite particles can be recycled and reshaped for reuse.

[0082] Test Example 2

[0083] refer to Figure 2 The metatitanate ion sieve powder was observed by SEM and TEM, and the metatitanate ion sieve composite particles were observed by SEM. Figure 2 middle This is the SEM image of metatitanate ion sieve powder. Figure 2 middle This is the TEM image of metatitanate ion sieve powder. Figure 2 middle This is the SEM image of the cross section of the metatitanate ion sieve composite particles. Figure 2 middle This is an enlarged SEM image of the cross section of the metatitanate ion sieve composite particles.

[0084] The SEM characterization of the titanate ion sieve powder showed that it had a cubic structure, a complete crystal structure and uniform size, with an average grain size of 100 nm; the TEM characterization of the titanate ion sieve powder showed that it had a layered structure.

[0085] In addition, SEM characterization of the titanate ion sieve composite particles shows that a porous network structure is formed inside the titanate ion sieve composite particles, which enables the adhesive to wrap the titanate ion sieve powder grains well and improve the overall mechanical strength. Its rich microporous structure can ensure its contact area with the brine, increase the mass transfer rate, and realize continuous lithium extraction operation.

[0086] Test Example 3

[0087] Solid phase reactions were carried out at different temperatures to obtain various ion sieve precursors, lithium titanate, and metatitanate ion sieve composite particles prepared from various ion sieve precursors, respectively, were subjected to lithium ion adsorption tests. The test results are as follows: Figure 3 shown.

[0088] When the calcination temperature of the ion sieve precursor lithium titanate is 973K, 998K, and 1023K, the adsorption amount of lithium ions by the metatitanate ion sieve composite particles is not less than 28mg / g, but when the calcination temperature of the ion sieve precursor lithium titanate exceeds 1073K, the adsorption amount of lithium ions by the metatitanate ion sieve composite particles drops sharply, which indicates that the grains have agglomerated, the active sites have decreased, and the adsorption performance has decreased. In addition, it can be seen from the right coordinate axis that the titanium loss gradually decreases with the increase of the calcination temperature of the ion sieve precursor lithium titanate, and is maintained between 0.11-0.66%, but if the calcination temperature of the ion sieve precursor lithium titanate is too low, there will be a higher titanium loss.

[0089] Therefore, considering the lithium ion adsorption and titanium loss, the calcination temperature of lithium titanate, the precursor of the ion sieve, was set at 1023K. Correspondingly, the capacity of the metatitanate ion sieve composite particles to adsorb lithium ions was 28.13mg / g, and the titanium loss was 0.193%. In addition, an amplification experiment was carried out under 1023K conditions, and 100g of metatitanate ion sieve composite particles were prepared and tested for lithium ion adsorption. As shown in the figure, it can be seen that the lithium ion adsorption and titanium loss remain constant, indicating that this process can be scaled up to meet the large-scale operation of lithium extraction from brine.

[0090] Test Example 4

[0091] A predetermined amount of metatitanate ion sieve composite particles was placed in a pseudo-brine solution containing lithium ions, calcium ions, magnesium ions, potassium ions and sodium ions with a cation concentration of 20 mmol / L, and an ammonia-ammonium chloride buffer solution was used to adjust the pH to 9.2. The adsorption amount of the metatitanate ion sieve composite particles on different cations was measured. The measurement results are as follows: Figure 4 shown.

[0092] As can be seen from the figure, the adsorption capacity of lithium ions by the metatitanate ion sieve composite particles is significantly better than that of other co-existing ions, indicating that the prepared metatitanate ion sieve composite particles have a higher selectivity for lithium ions.

[0093] Since the titanate ion sieve composite particles need to use hydrogen ions to replace the lithium ions in the ion sieve precursor lithium titanate during the preparation process, the formed titanate ion sieve composite particles only allow cations with an ionic radius less than or equal to that of lithium ions to pass through, and the ionic radius of lithium ions in the solution is 0.076nm, which is smaller than the ionic radius of calcium ions with an ionic radius of 0.100nm, potassium ions with an ionic radius of 0.138nm, and sodium ions with an ionic radius of 0.102nm. Although the magnesium ions with an ionic radius of 0.072nm are similar to the ionic radius of lithium ions, the hydration energy of magnesium ions is greater than that of lithium ions. Magnesium ions require higher energy to dehydrate through the lattice on the surface of the ion sieve. Therefore, magnesium ions are more difficult to be adsorbed by the titanate ion sieve composite particles than lithium ions.

[0094] Test Example 5

[0095] The same amount of metatitanate ion sieve powder and metatitanate ion sieve composite particles were placed in a lithium-containing solution to measure the adsorption of lithium ions by both. The test results are as follows: Figure 5 shown.

[0096] As can be seen from the figure, the amount of lithium ions adsorbed by the metatitanate ion sieve composite particles is lower than that by the metatitanate ion sieve powder. This is because when the metatitanate ion sieve composite particles are made, the adhesive covers part of the adsorption sites on the surface of the metatitanate ion sieve powder grains. Since the adhesive has good hydrophilicity, it has little effect on the adsorption of lithium ions. In addition, by adding pore-forming agents and acid washing to remove impurities, the metatitanate ion sieve composite particles present a rich microporous structure to improve their adsorption efficiency, thereby increasing the lithium extraction rate.

[0097] It should be understood by those skilled in the art that the embodiments of the present invention described above and shown in the accompanying drawings are only examples and do not limit the present invention. The advantages of the present invention have been fully and effectively achieved. The functional and structural principles of the present invention have been demonstrated and explained in the embodiments, and the embodiments of the present invention may be deformed or modified in any way without departing from the principles.

Claims

1. A method for preparing and forming a titanium-based lithium ion sieve, characterized in that: The preparation and molding method of the titanium-based lithium ion sieve comprises: (S1) Anatase titanium dioxide is obtained by calcining and dehydrating industrial grade metatitanic acid; (S2) performing a solid phase reaction of anatase titanium dioxide and a reaction material, lithium carbonate, in a molten salt medium to obtain an ion sieve precursor, lithium titanate; (S3) acid leaching lithium titanate, an ion sieve precursor, and centrifuging, drying, and grinding to obtain metatitanate ion sieve powder; (S4) Titanate ion sieve powder, a binder, a pore-forming agent and an organic solvent are mixed and dispersed into an aqueous phase after mixing to form impurity-containing titanium ion sieve composite particles, and the impurities are removed by acid washing and neutralization treatment to obtain titanium ion sieve composite particles.

2. The method for preparing and forming the titanium-based lithium ion sieve according to claim 1, characterized in that: The calcination temperature of the step (S1) is 873.15-923.15K, and the calcination time is 3-5 hours.

3. The method for preparing and forming the titanium-based lithium ion sieve according to claim 1, characterized in that: The step (S2) comprises the following steps: (S21) grinding and mixing anatase titanium dioxide, a reaction material lithium carbonate and a molten salt medium to obtain a molten salt mixed system reaction material; (S22) The molten salt mixed system reactants are calcined to react and obtain the ion sieve precursor lithium titanate.

4. The method for preparing and forming the titanium-based lithium ion sieve according to claim 3, characterized in that: The molten salt medium includes lithium chloride and lithium hydroxide, the molar ratio of the reaction materials lithium carbonate to anatase titanium dioxide is 1:1, and the molar ratios of lithium chloride and lithium hydroxide to anatase titanium dioxide in the molten salt medium are 1.53-1.81:1 and 0.27-0.33:1 respectively.

5. The method for preparing and forming the titanium-based lithium ion sieve according to claim 3 or 4, characterized in that: The calcination temperature in the step (S22) is 1023.15-1073.15K, and the calcination time is 8-10 hours.

6. The method for preparing and forming the titanium-based lithium ion sieve according to claim 4, characterized in that: The step (S3) comprises the following steps: (S31) mixing the ion sieve precursor lithium titanate with hydrochloric acid for desorption, taking out the acid leaching solution containing lithium chloride obtained by desorption of the upper layer and adding hydrochloric acid to repeat desorption to obtain a layered powder product after desorption; (S32) The desorbed layered powder product is centrifuged to obtain a titanate ion sieve powder block, and the titanate ion sieve powder block is dried and ground in turn to obtain a titanate ion sieve powder.

7. The method for preparing and forming the titanium-based lithium ion sieve according to claim 6, characterized in that: The extracted acid leaching solution containing lithium chloride is evaporated and crystallized to obtain lithium chloride, which is used as the molten salt medium required for step (S21).

8. The method for preparing and forming the titanium-based lithium ion sieve according to claim 1, characterized in that: The step (S4) comprises the following steps: (S41) mixing the titanate ion sieve powder, the binder, the pore-forming agent and the organic solvent to obtain a mixed slurry; (S42) sucking the mixed slurry and injecting it into water to form impurity-containing metatitanate ion sieve composite particles in the water phase; (S43) The impure titanate ion sieve composite particles are impregnated with hydrochloric acid and then washed with a weak alkaline aqueous solution to obtain neutral titanate ion sieve composite particles.

9. The method for preparing and forming the titanium-based lithium ion sieve according to claim 8, characterized in that: The adhesive is implemented to include polyvinyl butyral and polyacrylonitrile, the pore-forming agent is implemented as lithium carbonate powder, the organic solvent is implemented as N,N-dimethylacetamide, the titanate ion sieve powder is 11.7-14.3g, the corresponding polyvinyl butyral is 3.15-3.85g, the polyacrylonitrile is 0.45-0.55g, the lithium carbonate powder is 0.27-0.33g, and the N,N-dimethylacetamide is 16.2-19.8ml.

10. The method for preparing and forming the titanium-based lithium ion sieve according to claim 9, characterized in that: Waste titanate ion sieve composite particles are recovered, dried and the content of titanate ion sieve powder therein is measured, dissolved by an organic solvent, a pore-forming agent is added according to a predetermined proportion, and titanate ion sieve powder is added according to the difference between the predetermined proportion and the calculated titanate ion sieve powder to mix them, and then steps (S42) and (S43) are performed to obtain new titanate ion sieve composite particles.

Citation Information

Patent Citations

  • Preparation method of titanium lithium ion sieve

    CN117772123A

  • Preparation method of titanium lithium ion sieve for extracting lithium from salt lake

    CN118491498A